Does toxic stress impact paediatric dental procedures? An integrative review - Victor Cavallaro Bottesini; Gabriel Florio Cairo; Gabriel Marcelino; Danilo Antonio Duarte (Arbu Academic Publishing, 2021)
Toxic stress is defined as strong, repetitive stress with prolonged activation, without the child having the support of an adult caregiver. It is plausible that invasive and complex paediatric interventions produce or contribute to the development of toxic stress. This article aims to evaluate, discuss and synthesize the association between toxic stress and paediatric dental clinical practice through an integrative review of studies published in several databases. The results of this study allow us to state that this subject is little explored in the dental literature and, therefore, that it is essential to encourage clinical studies and specific research. The expansion of these studies will provide health professionals with scientific evidence regarding the implementation of proper clinical practice, thus reducing or even eliminating the development of toxic stress.